Penolakan China terhadap Arbitrase Filipina atas Penyelesaian Klaim Laut China Selatan - Amir, Firdaus; Yuniati, Sri; Hara, Abubakar Eby (e-Sospol, 2017)
Abstract On January 22, 2013, the Philippines had submitted an arbitration proposal to the international court of arbitration. The proposal was intended to sue China's claim over the nine-dash line through the map which was considered to be an overlapping claim toward sovereignty of some countries in the South China Sea. China considered that the Philippine’s initiative in resolving these issues through arbitration was a wrong option. China also considered that the Philippines had broken up the consensus of Declaration on the Conduct (DOC) that took the initiative to solve the problems of the South China Sea through peaceful measures. Therefore, China had declared to refuse to participate in the one-sided tribunal. This research aimed to identify China’s reasons to refuse to participate in the arbitration court. The research applied literature research and interviews. The results showed that China refused to participate in the arbitration for two reasons. First, China believed its sovereignty of South China Sea. Second, China considered this one-sided justice would take it to defeat because the tribunal would only be based on different interpretations from the way of acquisition of China’s territorial sovereignty.